Negative affect and respiratory sinus arrhythmia are differentially related to social anxiety and autism features in autistic preschoolers contrasted to fragile X syndrome - Wall, Carla A.; Roberts, Jane E. (Frontiers in Psychiatry, 2023)
Autism spectrum disorder is a highly heterogeneous and complex disorder with co-occurring disorders commonplace. This presents tremendous diagnostic challenges given the phenotypic overlap between autism and other diagnoses, including social anxiety, as well as variance in specific genetic disorders like fragile X syndrome (FXS). Biobehavioral measurement approaches integrate behavioral and biological data, and by so doing have the potential to address diagnostic challenges and shed light on the mechanisms underlying social impairments. The present study utilized a biobehavioral approach to evaluate how biologically based indices of baseline respiratory sinus arrhythmia (RSA) and temperamental negative affect differ and predict autism and anxiety in a sample of 120 preschoolers with non-syndromic autism (nsASD) with co-occurring intellectual impairment, FXS, and neurotypical development. Results indicated that children with nsASD display elevated negative affect compared to both FXS and neurotypical controls which did not differ from each other, and females exhibited more negative affect relative to males. Interestingly, elevated negative affect predicted social anxiety, but not ASD in FXS. Baseline RSA did not differ across the groups; however, reduced RSA predicted elevated autism severity for the nsASD group but not those with FXS or neurotypical development. Taken together, biobehavioral markers differentiated the groups in discrete ways that advance our understanding of autism and promote improved diagnostic clarity using objective measurement. These findings inform our understanding of the mechanisms behind these disorders.